Normal variants in patients consulted in the Dermatology Clinic for lesions of the male external genitalia - Michajłowski, Igor (Polish Urological Association, 2012)
INTRODUCTION: So far there have been no papers analyzing the incidence of ‘non-pathological’ lesions or normal variants on the male external genitalia. Subsequently, the number of patients consulted due to the presence of such lesions remains unknown. The aim of the study was to estimate the incidence of normal variants in patients who were consulted due to lesions on the skin or mucosa of the male external genitalia. MATERIAL AND METHODS: The study group consisted of 400 males, aged 3-91, who were consulted due to lesions on the genitalia in the Department of Dermatology, Venereology and Allergology of the Medical University of Gdańsk. RESULTS: The most common lesions were hyperpigmentation of the median raphe of the penis and scrotum (85.6%), pearly penile papules (24%), and prominent veins (24%). Sebaceous hyperplasia or ectopic sebaceous glands were revealed in 9% of patients, respectively. Melanocytic nevi were diagnosed with similar frequency (9.5%), whereas skin tags more rarely (7%). Other ‘non-pathological’ lesions were diagnosed in a considerably lower number of patients. In 32 patients (8% of all patients) the reason of admission to the Clinic was just the presence of some ‘non-pathological’ lesions. Pearly penile papules were found to be the most common condition, occurring in 78.1% patients. CONCLUSIONS: Normal variants represent a substantial percentage of generally asymptomatic lesions and the only indication for their removal is cosmetic discomfort or venerophobia.